Rujukan terma kerajaan tempatan (Local government reference of terms) / Suzei Mat Nurudin, Nor Suhaiza Md Khalid and Zarina Mohd Zain - Mat Nurudin, Suzei; Md Khalid, Nor Suhaiza; Mohd Zain, Zarina (Universiti Teknologi MARA, 2020)
The local government or also known as the local authority is the last tier and most important unit in the government's administrative structure in Malaysia after the federal and state governments. Local government is fully responsible for the delivery of services as well as the provision of basic facilities to the local people within its administrative area that has been designated by the state government. The existence of local government acted as a facilitator to the federal government and the state government because the roles and responsibilities held by the local government are very large and essential to the nation's development. This study discussed students' understanding of local government where the average between people and students is particularly confused about the concepts that are often used in the local government as well as local government-related jurisdictions. With the creation of these Pocket Dictionary on local Government, Glossary of local government terms and QR Code Mode for Local Government Terms Word Index, it help students and the local people to better understand the local government in Malaysia by knowing the concepts related.